Citizen Journalism Berbasis Jemaat sebagai Model Penguatan Literasi Media Komunitas di GMIT Koinonia Kupang - Yeheskial A. Roen; Sari A. Natonis; Yuri Sandra Fa'ah (Yayasan Literasi Sains Indonesia, 2026)
The low participation of congregants in community-based information production has limited the role of church digital media as a space for communication and social representation within the community. This condition was identified at GMIT Koinonia Kupang, where church digital media was primarily used for internal documentation with minimal congregational involvement in community content production. This community service program aimed to strengthen media literacy and digital participation among congregants through a community-based citizen journalism model. The program employed a participatory approach through workshops, straight news writing training, and mentoring in community media management. The activities involved 50 participants consisting of youth members, church elders, and ministry commissions of GMIT Koinonia Kupang. The results demonstrated an improvement in participants’ understanding of citizen journalism, news-writing techniques, and community digital media management. The program also encouraged a transformation in congregational participation from passive information consumers into active community content producers. Beyond improving technical journalistic skills, the program strengthened the role of church digital media as a space for social participation, local narrative representation, and the reinforcement of congregational collective identity. Therefore, community-based citizen journalism can be developed as a contextual, participatory, and sustainable model for empowering church community media in the digital era.